Study of the Blast Pattern to Improve the Effect on Fragmentation in a Small Sized Silica Mine in Korea - Jang, Hyong Doo; Yang, H.; Kim, J.; Ko, Y.; Kim, S.; Mun, H.; Kim, W. (Korean Society of Explosives and Blasting Engineering, 2012)
Fragmentation is one factor to affect productivity and economic efficiency of mine. Authors investigate the blasting pattern and improve it step by step while observing the fragmentation results. Final pattern was suggested and the fragmentation improved 24% compared to traditional pattern, with 50% is passing rate.